Hormatilah Istrimu: Sebuah Penafsiran Terhadap 1 Petrus 3:7 - Sembiring, Raharja; Butarbutar, Rut Debora (Faculty of Theology Duta Wacana Christian University, 2021)
Abstract1 Peter 3:1â€“7 is a dilemmatic text. The word hupotassÅ or â€˜subject toâ€™ in this passage is often used to justify female subordination.This article uses the identity of 1 Peterâ€™s addressee, paroikos kai parepidÄ“mos, as a hermeutical framework to get new ideas on the meaning of relations between men and women. The existence of verse 7 in haustafelnâ€™s advice of 1 Peter 3:1â€“7 indicates that the spirit of equality has been echoed by the author in the Greco-Roman patriarchal society. A husband who was already a believer is a potential point for constructing gender equality and, at the same time, protecting women in a patriarchal cultural circle. AbstrakTeks 1 Petrus 3:1â€“7 merupakan teks yang dilematis. Kata hupotassÅ atau â€˜tundukâ€™ dalam perikop ini sering digunakan sebagai pembenaran bagi subordinasi perempuan. Tulisan ini menggunakan identitas penerima surat 1 Petrus, paroikos kai parepidÄ“mos, sebagai hermeneutical framework atau bingkai kerja penafsiran untuk mendapatkan gagasan baru atas makna relasi laki-laki dan perempuan. Keberadaan ayat 7 dalam nasihat haustafeln 1 Petrus 3:1â€“7 menandakan bahwa jiwa kesetaraan sudah mulai didengungkan oleh pengarang dalam masyarakat patriarki Yunani-Romawi. Suami yang sudah percaya adalah celah yang potensial untuk membumikan kesetaraan jender dan sekaligus melindungi perempuan dalam lingkaran budaya patriarki.